Transstadial Transmission of Borrelia turcica in Hyalomma aegyptium Ticks - Kalmár, Zsuzsa (PLoS One, 2015)
Borrelia turcica comprises the third major group of arthropod-transmitted borreliae and is phylogenetically divergent from other Borrelia groups. The novel group of Borrelia was initially isolated from Hyalomma aegyptium ticks in Turkey and it was recently found in blood and multiple organs of tortoises exported from Jordan to Japan. However, the ecology of these spirochetes and their development in ticks or the vertebrate hosts were not investigated in detail; our aims were to isolate the pathogen and to evaluate the possibility of transstadial transmission of Borrelia turcica by H. aegyptium ticks. Ticks were collected from Testudo graeca tortoises during the summer of 2013 from southeastern Romania. Engorged nymphs were successfully molted to the adult stage. Alive B. turcica was isolated from molted ticks by using Barbour-Stoenner-Kelly (BSK) II medium. Four pure cultures of spirochetes were obtained and analyzed by PCR and sequencing. Sequence analysis of glpQ, gyrB and flaB revealed 98%–100% similarities with B. turcica. H. aegyptium ticks collected from T. graeca tortoises were able to pass the infection with B. turcica via transstadial route, suggesting its vectorial capacity.